Cultivating the Pancasila Student Profile in Early Childhood Using the Garuda Book: An Innovative Method in Indonesian Educational Practices - Masitah, Widya; Sitepu, Juli Maini; Raniyah, Qaulan (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This study examines the effectiveness of the Garuda Book, a tailored educational tool for instilling the Pancasila Student Profile in early childhood education within Indonesia’s Independent Curriculum framework. Utilizing a Research and Development (R&D) approach, this research involved creating, implementing, and evaluating the Garuda Book in an early childhood educational setting at RA Nurul Hadina. The study’s methodology incorporated the development of project activities linked to the curriculum, including "I Love the Earth" and "I Love Indonesia," with the book designed for durability and child appeal. Data collection entailed various questionnaires assessing media and material validity and the effectiveness of the Garuda Book in imparting Pancasila values. Results indicated a significant improvement in children’s understanding and embodiment of Pancasila values post-intervention, as evidenced by increased scores in assessments related to faith, diversity, cooperation, independence, critical reasoning, and creativity. However, challenges such as teachers’ limited understanding of the independent curriculum were noted, necessitating further training. This study’s findings underscore the potential of contextually relevant educational tools like the Garuda Book in early childhood education, contributing substantially to pedagogical practices aimed at value formation. Future research could explore such tools’ long-term impacts and adaptability across diverse educational contexts.